Modification of Demonstrative Methods: Increased Understanding of the Value of Place in Children with Special Needs - Sinabutar, Fernan; Panjaitan, Binur (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
Improving Students' Understanding of the Value of Places Through Demonstration Methods in Students of Class IV-C Sekolah Luar Biasa Negeri Doloksanggul School Year 2022/2023. The purpose of this study is to describe the improvement of students' understanding of the material of place values through the Demonstration method so as to improve student learning outcomes in Sekolah Luar Biasa Negeri Doloksanggul, Humbang Hasundutan Regency. This class Action Research was conducted in Sekolah Luar Biasa Negeri Doloksanggul Humbang Hasundutan Regency. The type of action in this study is in the form of concrete actions, namely guiding students in the implementation of learning activities through the Demonstration method. The research was conducted in semester I, precisely in September-November 2022. This classaction research sub j ek is students in Sekolah Luar Biasa Negeri Doloksanggul Humbang Hasundutan Regency with a total of 4 students. The results showed that students' understanding of the venue value material increased after applying the Demonstration method thereby improving student learning outcomes. The average student learning outcomes increased after applying the Demonstration method to the Place Value material, where the average student learning outcomes in the first cycle of 45.00 increased to 80.00 in cycle II.